Feasibility study on the establishment of an All Ladies Centre in Singapore - Nadiah Mohd Said (2008)
This study aims to determine the feasibility of setting up an All Ladies Centre (ALC) in Singapore. The analysis is based on the survey results garnered from respondents. Aside from this, a business environment analysis is also conducted and the tools used to analyse this section are PEST, Porter’s five forces and SWOT analysis.